Scientific research misconducts : An overview - Arzmi, Mohd Hafiz (IIUM Journal of Orofacial and Health Sciences, 2021)
Research misconduct is defined as fabrication, falsification, or plagiarism in proposing, performing, or reviewing research, or in reporting research results (Anderson, 2013; Breen, 2016; Resnik, 2019). It can occur at many stages of the research process. These include during proposal preparation, data collection, analysis and publication (Amin et al., 2012). The previous studies reported that 2,047 articles were retracted from PubMed in May 2012, with 67% of the articles due to misconduct (Dal-Ré et al., 2020). Besides, the percentage of retracted papers in the year of 2012 were reported to increase by 10-fold compared to the total articles retracted in 1975 (Fang et al., 2012). According to Liu and Chen (2018), the data from Retraction Watch on the 31st July 2017 revealed that the US, China, Germany, Japan and India were the top six countries that had articles retracted.